Diet Quality and Associations with Food Security among Women Eligible for Indiana Supplemental Nutrition Assistance Program-Education - Rivera, Rebecca L (J Nutr, 2020)
BACKGROUND: The diet quality among adults receiving nutrition education lessons through Supplemental Nutrition Assistance Program-Education (SNAP-Ed) is currently unknown. OBJECTIVES: The objectives of this study were to characterize the diet quality of Indiana SNAP-Ed-eligible women; estimate their mean usual intake of fruits, vegetables, dairy, and whole grains compared to Dietary Guidelines for Americans (DGA) recommendations; and determine if these dietary outcomes differed by food security status. METHODS: SNAP-Ed paraprofessionals recruited participants from August 2015 to May 2016 for this secondary analysis of cross-sectional data collected as the baseline assessment for a randomized controlled trial. Participants were SNAP-Ed-eligible women aged ≥18 y interested in nutrition education lessons. Dietary outcomes were assessed by one or two 24-h dietary recalls. The Healthy Eating Index (HEI)-2010 was used to characterize diet quality. Mean usual intake of food groups was estimated using the National Cancer Institute Method. Food security status was classified using the US Household Food Security Survey Module. Data were analyzed in October 2019. RESULTS: Mean ± SEM HEI-2010 total score was 42 ± 0.9 for the study sample. Mean ± SE usual intake of servings of fruits (0.61 ± 0.08 cups [144.32 ± 18.93 mL]), vegetables [1.4 ± 0.10 cups (331.2 ± 23.66 mL)], dairy [1.5 ± 0.11 cups (354.88 ± 26.02 mL)], and whole grains [0.48 ± 0.06 ounces (13.61 ± 1.70 g)] did not differ by food security subgroup. Mean HEI-2010 total score was significantly higher by 4.8 ± 2.0 points for the food-secure than for the food-insecure subgroup (P = 0.01). Mean HEI-2010 component scores were 1.1 ± 0.5 points higher for whole grain (P = 0.01) and 1.0 ± 0.5 points higher for dairy (P = 0.05) in the food-secure than in the food-insecure subgroup. The proportions of the study sample not meeting the DGA recommendations for food group intake were ≥85% for both food-secure and -insecure subgroups. CONCLUSIONS: Indiana SNAP-Ed-eligible women reported poor diet quality, highlighting their need for nutrition interventions aiming to improve food security and diet as per DGA recommendations in low-income populations.